Hubungan Berat Badan Lahir (BBL) Dengan Kejadian Asfiksia Neonatorum Di Ruang Kebidanan RSD Demang Sepulau Raya Kabupaten Lampung Tengah: Periode Juni 2019-Mei 2020 - Sugiarti, Wahidiyah; Lubis, Efrilayani (Akademi Kebidanan Bunga Husada Samarinda, 2021)
The neonatal mortality rate (NMR) is an indicator of public health level. According to WHO, there were 3.6 million (3%) of 120 million neonatal suffered asphyxia and 1 million were death in 2007. The asphyxia prevalence in Demang Sepulau Raya public hospital increased from 9.79% in period of June 2019 – May 2020 to 10.3% , and this was coincident with increasing prevalence of low birth weight of 116 from 100 cases. This research was purposed to find out the correlation between birth weight and asphyxia neonatorum in Demang Sepulau Raya public hospital of Lampung Tengah regency in period of June 2019 – May 2020. This was an analytic research with cross sectional approach. Population was all 846 neonatal delivered in Demang Sepulau Raya public hospital of Lampung Tengah regency in period of June 2019 – May 2020, and samples were total population.The results that from 846 neonatal, 87 (10.3%) suffered asphyxia, 128 (15.13%) were delivered with abnormal birth weight. The statistic test obtained p-value 0.000 and OR 19.69 and this meant that there was a significant correlation between birth weight and asphyxia neonatorum incidents in Demang Sepualu Raya public hospital. Neonatal with abnormal birth weight had 20 fold risk of experiencing asphyxia compared with neonatal with normal weight. The researcher expected midwifes to give qualified antenatal care and give information about the hints of pregnancy risk, delivery, and neonatal, so that the risk factors can be reduced. The researcher also suggested midwifes and nurses to be more competence in handling complicated infants and joining trainings of complicated infant management.